Analysis of gingival plaque index and oral hygiene of patients with regard to smoking - Patrícia Petromili Nordi Sasso Garcia; Pedro Gregol da Silva; Nára Rejane Santos-Pereira; André Afif Elossais; Taís Cristina Dinelli Esperança; Welingtom Dinelli (Faculdade São Leopoldo Mandic, 2008)
Objective: To make a clinical evaluation of periodontal alterations caused by cigarettes in smoker and non-smoker patients from two aspects: gingival plaque index and oral hygiene. Methods: Eighty patients of both sexes, ranging between 20 and 50 years of age, were selected and divided into four experimental groups (non-smoker patients without esthetic restorations, non-smoker patients with esthetic restorations, smoker patients without esthetic restorations, smoker patients with esthetic restorations). Results: The patients without restorations, irrespective of whether they were smokers or not, presented a lower gingival plaque index than the patients with restorations; that is, the presence of restorations exerts a strong influence on the increase in bacterial and gingival plaque indexes. With regard to oral hygiene, of the 40 smoker patients examined, many had been smoking for many years; in the majority of cases, around 20 cigarettes/day. Of the 80 patients examined (smokers and non-smokers), around 50% informed that they brushed their teeth three times a day, and 55 patients (over 50%) informed that they visited the dentist periodically. Of the 80 patients examined (smokers and non-smokers), only 17 returned to the dental consulting room every six months, while 26 patients informed that they went once a year. Balance was also found between smokers and non-smokers with regard to the presence of bad breath. (halitosis) Conclusion: Restorations had a strong influence on the increase in the bacterial and gingival plaque indexes, and over 50% of the patients examined informed that they visited the dentist periodically. As regards the presence of bad breath, it was found that around 40% of patients affirmed being aware of it.